Determinants of financial distress: evidence from listed GN3 companies in Bursa Malaysia / Wan Nur Awatif Wan Zulkifikri - Wan Zulkifikri, Wan Nur Awatif (Faculty of Business Management, 2017)
This study investigates thefactors that influence the financial distress towards the companies listed in Guidance Note 3 (GN3). The issue of this study is to know and get a clear picture on the performance of the company after being listed in GN3. Besides that, the purpose of this study is to have a clear view on the relationship between the dependent variable of Return on Asset (ROA )was used to measure financial performanceand independent variables of Debt ratio (DR), Total Asset Turnover ratio (TATO), Current ratio (CR), and Net Profit Margin (NPM). A population of 113 companies in ACE Market, a sample of 6 companies that were listed in GN3 was selected. The period under study was from 2009 to 2013. The observation data are collected for 30 observations of yearly data of financialstatement and balance sheet found in Bursa Malaysia. The data has been analysed by using Stata 11 to do descriptive analysis, fixed effect model regression, random effect model regression and multiple regression. Based on the results, 2out of 4variablesare significant and majority of the variable have positive relationship with financial performance. Financial performance will be affected when financial distress increase. In order to ensure the shareholders confidence, the companies need to reduce financial distress by ensuring financial stability in GN3’s company (Kariuki,H.N.,2013)